2010
DOI: 10.1080/14616680903493647
|View full text |Cite
|
Sign up to set email alerts
|

‘Pulling up the Tent Pegs?’ The Significance and Changing Status of Coastal Campgrounds in New Zealand

Abstract: This article considers the importance of beach-front campgrounds in NewZealand, both as physical sites offering affordable public access to coastal environments, and as sites of social and psychological meaning. It traces the evolution of coastal campgrounds from 'freedom camping', to more formal (if initially basic) facilities, to the development of relatively up-market holiday parks offering a wide range of services and accommodation options. While camping styles and options changed significantly over the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 15 publications
1
46
0
1
Order By: Relevance
“…Yet, a too-overt focus on otherness could neglect the significance of familiarity in tourism. We found familiar and comfortable social environments to be important to many proximity tourists in Friesland, in line with findings on camping tourists elsewhere (Blichfeldt, 2004;Collins & Kearns, 2010;Mikkelsen & Cohen, 2015) and secondhome tourists (M€ uller, 2006). Thus, tourism policy should be sensitive to the importance of mundane activities in tourism, doing nothing as a way to 'vacate' (Blichfeldt & Mikkelsen, 2013) and the often strong attachments tourists develop to the destinations they visit.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…Yet, a too-overt focus on otherness could neglect the significance of familiarity in tourism. We found familiar and comfortable social environments to be important to many proximity tourists in Friesland, in line with findings on camping tourists elsewhere (Blichfeldt, 2004;Collins & Kearns, 2010;Mikkelsen & Cohen, 2015) and secondhome tourists (M€ uller, 2006). Thus, tourism policy should be sensitive to the importance of mundane activities in tourism, doing nothing as a way to 'vacate' (Blichfeldt & Mikkelsen, 2013) and the often strong attachments tourists develop to the destinations they visit.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…Aesthetic beauty, facilitation of desired recreational activities, escape from the everyday and experiences with family and friends were all key meanings identified by Wynveen et al (2010) in their study of recreational visitors to the Great Barrier Reef. A review of coastal camping in New Zealand identified the ability of undisturbed beaches to evoke feelings of awe, inspiration and fostering a sense of wonder (Collins & Kearns, 2010). This is a similar sentiment to that expressed by participants in this study in their description of the colours of the rock pools or the vast expanse and kilometres of coastline.…”
Section: Discussionmentioning
confidence: 49%
“…This is a similar sentiment to that expressed by participants in this study in their description of the colours of the rock pools or the vast expanse and kilometres of coastline. In addition was the sense of community that developed when regular campers returned to the same campground each time, thereby renewing acquaintances (Collins & Kearns, 2010;Garst, Williams & Roggenbuck, 2010). In this study, they formed important friendship groups based on shared experiences of camping and boating.…”
Section: Discussionmentioning
confidence: 99%
“…As Veijola and Falin (2014: 14) argue, mobile dwellings 'allow people more personal freedom in how they perform their neighbouring than permanent neighbourhoods do.' In this case, the caravan site allows for casual chats and social interaction more so than the private spaces they may experience in their home neighbourhood (see also Collins and Kearns, 2010). However, this does not mean that caravanners wish to be with other people all the time; rather, a 'good holiday' included spending time close to others, reflecting a non-obligated, casual sociality.…”
Section: We Have Our Next-door Neighbours From Home As Neighbours Hermentioning
confidence: 99%